Results and Factors Affecting Early Outcome of Fenestrated and/or Branched Stent Grafts for Aortic Aneurysms. Issue 1 (January 2015) - Marzelle, J.; Presles, E.; Becquemin, J. P.
<x xml:space="preserve">Abstract</x> Objective: To present results and to identify predictive factors of early outcome after fenestrated and/or branched endovascular repair (f/b-EVAR) for complex aortic aneurysms, abdominal (AAA) and thoracoabdominal (TAAA). Background: Feasibility of f/b-EVAR for complex aneurysms is now established, but little is known about which patients will benefit from this technique. Methods: Univariate and multivariate analysis of preoperative and intraoperative factors on postoperative mortality and complications was performed on 268 patients (group 1: juxta- and pararenal AAA; group 2: suprarenal and TAAA IV; group 3: TAAA I, II, III) enrolled in a prospective multicenter trial of f/b-EVAR. Results: Thirty-day mortality, in-hospital mortality (IM), and combined mortality and severe complications (CMSC) rates were 6.7%, 10.1%, and 22.0%, respectively. Group belonging (2 or 3 vs 1) was the only preoperative predictive factor of CMSC [hazard ratio (HR) = 2.10; 95% confidence interval (CI): 1.26–3.48; P = 0.0043]. Occurrence of a technical complication and duration of intervention significantly influenced both IM (HR = 4.39; 95% CI: 2.05–9.38; P = 0.0001) and CMSC (HR = 3.07; 95% CI: 1.84–5.11; P < 0.0001). Postoperative events associated with increased IM were spinal cord ischemia (HR = 9.46; 95% CI: 3.98–22.47; P < 0.0001), hemodialysis (HR = 27.44; 95% CI: 12.63–59.61; P < 0.0001), and reintervention (HR = 4.45; 95% CI: 2.03–9.73; P = 0.0002). Conclusions: Although promising, f/b-EVAR still carries a significant rate of mortality and complications, mostly related to the complexity of the procedure. In these complex cases, new strategies should be investigated to improve outcomes.